1999
DOI: 10.1109/75.819417
|View full text |Cite
|
Sign up to set email alerts
|

X-band RF MEMS phase shifters for phased array applications

Abstract: In this letter, development of a low-loss radio frequency (RF) microelectromechanical (MEMS) 4-bit X-band monolithic phase shifter is presented. These microstrip circuits are fabricated on 0.021-in-thick high-resistivity silicon and are based on a reflection topology using 3-dB Lange couplers. The average insertion loss of the circuit is 1.4 dB with the return loss >11 dB at 8 GHz. To the best of our knowledge, this is a lowest reported loss for X-band phase shifter and promises to greatly reduce the cost of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(40 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Malczewski et al [43] also reported a two-stage 2-bit reflection-type delay line, with tapped delay line reflection terminations. The same transmission line medium, substrate and MEMS switches were used as with the earlier switchedline example [39].…”
Section: Phase Shiftersmentioning
confidence: 99%
“…Malczewski et al [43] also reported a two-stage 2-bit reflection-type delay line, with tapped delay line reflection terminations. The same transmission line medium, substrate and MEMS switches were used as with the earlier switchedline example [39].…”
Section: Phase Shiftersmentioning
confidence: 99%
“…3b) [16]. The phase noise generated in each arm of the 3-dB coupler is the same as Case 2 above, but is referenced to half of the signal power.…”
Section: Phase Shifters Based On Shunt Switchesmentioning
confidence: 99%
“…Besides the size advantage of this phase shifter, if their power and phasebandwidth capabilities are compared with phase shifters that use switched lines [14], reflection [15], or loaded * Correspondence: msengul@khas.edu.tr lines [16], it is acknowledged that high-pass/low-pass phase shifters are the best choice [12]. From the more complicated versions [17] to simple versions with pin diode switches [18], the usage of the high-pass/low-pass shifters has increased in the last 15 years.…”
Section: Introductionmentioning
confidence: 99%